Multiple meanings of resilience: Health professionals' experiences of a dual element training intervention designed to help them prepare for coping with error. Issue 2 (4th March 2021) - Janes, Gillian; Harrison, Reema; Johnson, Judith; Simms‐Ellis, Ruth; Mills, Thomas; Lawton, Rebecca
Abstract: Rationale, aims and objectives: Consistent data demonstrates negative psychological effects of caregiving on front‐line health professionals. Evidence that psychological resilience factors can help minimize distress and the potential for low‐cost interventions have created interest in resilience‐based development programmes; yet evidence of perceived value amongst health professionals is lacking. This study explored health professionals' experiences and perceptions of a novel, resilience‐based intervention designed to pro‐actively prepare staff for coping with error; to investigate their perceptions of what resilience meant to them, the relevance of the intervention, and impact of participation on ability to cope with error. Methods: Semi‐structured interviews 4‐6 weeks post intervention with 23 randomly selected participants from seven cohorts (midwives, paediatricians, obstetricians/gynaecologists, paramedics) and trainees (physician associates, mammographers, sonographers). Thematic analysis of interview data. Findings: Participants reported various interpretations of, and a shift in perception regarding what the concept of psychological resilience meant to them and their practice. These included for example, resilience as a positive or negative concept and their awareness and response to a range of personal, organizational and system factors influencing personal resilience. They valued the prophylactic, clinically relevant, interactive and applied nature of the intervention; having developed and applied valuable skills beyond the context of involvement in error, noting that individuals needed to be willing to explore their own coping mechanisms and human fallibility to gain maximum benefit. There was also consensus that whilst proactively developing individual level psychological resilience is important, so too is addressing the organizational and system factors that affect staff resilience which are outside individual staff control. Conclusion: Enhancing resilience appears to be considered useful in supporting staff to prepare for coping with error and the wider emotional burden of clinical work, but such interventions require integration into wider system approaches to reduce the burden of clinical work for health professionals.